2014
DOI: 10.1016/j.neuroscience.2013.11.057
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR-146a in dorsal root ganglia neurons of experimental diabetic peripheral neuropathy

Abstract: Sensory neurons mediate diabetic peripheral neuropathy. Using a mouse model of diabetic peripheral neuropathy (db/db mice) and cultured dorsal root ganglion (DRG) neurons, the present study showed that hyperglycemia downregulated miR-146a expression and elevated interleukin-1 receptor activated kinase (IRAK1) and tumor necrosis factor receptor-associated factor 6 (TRAF6) levels in DRG neurons. In vitro, elevation of miR-146a by miR-146a mimics in DRG neurons increased neuronal survival under high glucose condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…Additionally, miR-146a expression in the sensory neuron of DRG was much lower in 24-week-old diabetic db/db mice than that in non-diabetic mice (Wang et al, 2014). However, we found that Fig.…”
Section: Mir-146a-5p Expression In the Spinal Cord And Neuropathic Painmentioning
confidence: 48%
See 1 more Smart Citation
“…Additionally, miR-146a expression in the sensory neuron of DRG was much lower in 24-week-old diabetic db/db mice than that in non-diabetic mice (Wang et al, 2014). However, we found that Fig.…”
Section: Mir-146a-5p Expression In the Spinal Cord And Neuropathic Painmentioning
confidence: 48%
“…It was noteworthy that (1) although SNL increased miR-146a-5p levels at 10 and 21 days, these levels were not sufficient to significantly reduce the expression of the TRAF6, and overexpression miR-146a-5p is required to exert an analgesic effect; (2) intrathecal drug delivery can affect both spinal cord and DRG (Butler et al, 2005;Zhuang et al, 2006). Intrathecal miR-146a-5p mimic may also exert anti-nociceptive effect via regulating the function of TRAF6 and IRAK1 in the DRG (Wang et al, 2014).…”
Section: Mir-146a-5p Expression In the Spinal Cord And Neuropathic Painmentioning
confidence: 99%
“…Neural stem/progenitor cells Promote proliferation miR-25 [12]; miR-137 [13]; miR-184 [14]; miR-195 [15] Induce differentiation miR-9, siRNA-TLX [16]; let-7d [17]; miR-137 [13]; miR-184 [14]; miR-195 [15]; miR-34a [18]; lncRNA-BDNF-AS, siRNA-BDNF-AS [19] Mesenchymal stem cells Induce differentiation miR-9 [20]; miR-124 [21] Reduce differentiation miR-128 [22] Neuronal cells Inhibit cell death miR-223 [23]; miR-181c [24]; miR-592 [25]; miR-424 [26]; miR-23a-3p [27]; miR-23a/b, miR-27a/b, siRNA-Apaf-1 [28] Promote cell death miR-134 [29]; miR-200c [30]; miR-30a/b [31][32][33]; miR-124 [34]; miR-711 [35] Regulate degeneration and apoptosis miR-20a [36]; miR-29b [37]; miR-146a, siRNA-miR146a [38] Promote neurite outgrowth miR-7 [39]; miR-21 [40]; miR-222, siRNA-PTEN [41]; miR-8 [42]; miR-431 [43]; miR-145 [44]; lncRNA-uc.217 [45]; miR-138, siRNA-SIRT1 [46] Microglial cells Inhibit inflammation let-7c [47]; miR-124, siRNA-C/EBP-α [48] Promote pro-inflammation miR-155 [49] Inhibit activation let-7c-5p [50] Astrocytes P...…”
Section: Nervementioning
confidence: 99%
“…Following peripheral nerve injury, overexpression of miR-21 and miR-222 reduces apoptosis and enhances the viability of cultured dorsal root ganglion (DRG) neurons [40,41]. miR-146a mediates apoptosis in DRG neurons under hyperglycemic conditions [38].…”
Section: Neuronal Cellsmentioning
confidence: 99%
“…As intracellular miRNAs appear to be deregulated in this diabetic complication, it would be worthwhile to investigate whether circulating miRNAs could be potential biomarkers of this disease [68,69].…”
Section: Circulating Mirnas As Biomarkers To Assess Diabetic Complicamentioning
confidence: 99%